KELAS ASI : KELAS UNTUK IBU BEKERJA YANG MENYUSUI - Nor Indah Handayani; Novita Wulandari (STIKES NGUDIA HUSADA MADURA, 2022)
The cause of the emergence of nutritional problems in children under five is influenced by many interrelated factors. It is directly influenced by several things, namely the child does not get enough nutritious food at the age of five, the child does not get adequate nutritional care and the child suffers from an infectious disease. One of the causes of malnutrition is that babies do not receive full breast milk until the first 6 months of age. So that babies have a greater risk of gastrointestinal tract infections and respiratory infections than babies who are exclusively breastfed. This can lead to malnutrition in infants (Purwaniati, 2013). The results of WHO research (2005) states that 42 percent of the biggest causes of infant mortality in the world are malnutrition (58%). Babies need very high nutrients to maintain their life. The method used to carry out community service is by collecting data on the number of breastfeeding mothers in Mlajah Bangkalan. Health workers will be assisted or accompanied by cadres to run the ASI class program. As is well known, the role of the closest family is very important in providing motivation to breastfeeding mothers. Not only families, midwife assistants, namely cadres are also involved in providing education. So the main focus in this program is to provide knowledge to a mother as an implementer and to activate cadres by means of training on techniques that are important for breastfeeding mothers to be able to maintain or even increase milk production. uring the process of the ASI Class activities program, which consists of a cadre formation program, counseling, giving lactation medians, and the entire program runs smoothly.